Influence of gender determinants on informal care and health service utilization in Spain: Ten years after the approval of the equality law - Raquel Sánchez-Recio; Cristina García-Ael; Gabriela Topa (Administrative Sciences, 2021)
The existence of gender inequalities in health, in the use of health services, and in the development of informal care has been demonstrated throughout scientific literature. In Spain, a law was passed in 2007 to promote effective equality between men and women. Despite this, different studies have shown that the previous gender inequalities are still present in Spanish society. For all these reasons, the objective of this paper is to study the differences by sex in informal care and in the use of emergency care, and to identify the existence of gender inequalities in Spain 10 years after the adoption of the aforementioned equality law. In this case, we development a cross-sectional study based on the 2017 Spanish National Health Survey of the Spanish population aged 16 and over. To analyze the influence of gender determinants on informal care and emergency care utilization, logistic regressions were performed, model 1 was adjusted for age, and model 2 was further adjusted too by the variables of the Andersen care demand model. The results showed that informal care and the use of the emergency care continues to be higher in women than in men. Informal care in women was related to a higher level of education. In emergency care, the older the age, the lower the probability of utilization, and living in a rural municipality was related to a higher probability of utilization for both sexes. Finally, we concluded that there is still a need for studies that analyze gender inequalities in different contexts, such as the informal care and the use of health services. This is especially relevant in Spain, where economic changes have led to a change in roles, mainly for women, and new management strategies are needed to achieve equity in care and effective equality between men and women.
Keywords: 350; emergency services; gender; health care services; inequalities; informal care